THE INFLUENCE OF CORPORATE GOVERNANCE ON FINANCIAL REPORT FRAUD WITH COMPANY SIZE AS A MODERATING VARIABLE IN INFRASTRUCTURE, UTILITIES, AND TRANSPORTATION COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE DURING THE PERIOD 2019-2021 - Zirda Kurnia; Enggar Diah Puspa Arum; Rico Wijaya Z. (Transpublika Publisher, 2024)
The primary objective of this research is to examine the impact of corporate governance, as indicated by the board of commissioners, audit committee, and institutional ownership, on financial statement fraud. Additionally, this study aims to investigate the moderating role of company size in this relationship. The target population for this study comprises infrastructure, utilities, and transportation companies that are listed on the Indonesia Stock Exchange during the period of 2019-2021. The sample for this research was selected using a purposive sampling method, resulting in a total sample size of 60 companies. Logistic regression analysis and moderating regression analysis were employed to analyze the data. The findings of this study reveal that both the board of commissioners and the audit committee have a significant influence on financial statement fraud. However, institutional ownership does not exhibit a significant impact on financial statement fraud. Furthermore, the results indicate that company size plays a role in strengthening the relationship between the board of commissioners and the audit committee in terms of financial statement fraud. Conversely, company size weakens the relationship between institutional ownership and financial statement fraud.